Effects of Different Viscous Guar Gums on Growth, Apparent Nutrient Digestibility, Intestinal Development and Morphology in Juvenile Largemouth Bass, Micropterus salmoides - Liu, Yu; Zhang, Yumeng; Fan, Jiongting; Zhou, Hang; Huang, Huajing; Cao, Yixiong; Jiang, Wen; Zhang, Wei; Deng, Junming; Tan, Beiping (Frontiers in Physiology, 2022)
An 8-week feeding trial was conducted to investigate the effects of different viscous guar gum on the growth performance, nutrient apparent digestibility, intestinal development and morphology of juvenile largemouth bass. Four isoproteic and isolipidic diets (crude protein 42.5%, crude lipid 13.7%) to contain 8% cellulose (Control group), 8% low viscous guar gum with 2500 mPa•s (Lvs-GG group), 8% medium viscous guar gum with 5200 mPa•s (Mvs-GG group) and 8% high viscous guar gum with 6000 mPa•s (Hvs-GG group), respectively. Each diet was fed to quadruplicate groups of 40 fish (6.00 ± 0.01 g) per repetition. Dietary guar gum inclusion significantly decreased the weight gain rate, specific growth rate, protein efficiency ratio, protein productive value and lipid deposition rate, and these parameters decreased significantly with increasing guar gum viscous and were lowest in the Hvs-GG group. Dietary guar gum inclusion significantly decreased the apparent digestibility of dry matter, crude protein and crude lipid, and these parameters decreased significantly with increasing guar gum viscous and were lowest in the Hvs-GG group. The villus height and muscularis thickness in the guar gum groups were significantly higher than those in the control group, while the goblet cell relative number in the Mvs-GG and Hvs-GG groups and the microvillus height in the Lvs-GG and Hvs-GG groups were significantly lower than those in the control group. The expression level of IGF-1 in the guar gum groups and the expression level of GLP-2 in the Mvs-GG and Hvs-GG groups were significantly higher than those in the control group. These results indicated that guar gum diets adversely affected intestinal morphology, decreased intestinal digestive and absorptive enzyme activities, and caused poor nutrient digestibility and growth performance in juvenile largemouth bass. Moreover, the adverse effects of guar gum are closely related to its viscous, and high viscous guar gum produces more extreme negative impacts on juvenile largemouth bass.